Life Cycle Analysis of MACHU PICCHU FOODS chocolate - (:unkn) unknown (My University, 2026)
The Life Cycle Thinking or "Life Cycle Thinking" implies that different actors involved in the value chains of products and services have a responsibility and a role in guaranteeing a sustainable use of resources in said value chain, from cradle to the gr